Color data (RGB) of IODP Hole 386-M0089D - Michael Strasser; Ken Ikehara; Jeremy D Everest; Lena Maeda; Katharina Hochmuth; Hannah Grant; Margaret S Stewart; Noriaki Sakurai; Takahiro Yokoyama; Rui Bao; Piero Bellanova; Morgane Brunet; et al. (PANGAEA, 2025)
Color data obtained from split core sections from the above given hole of International Ocean Discovery Program (IODP) Expedition 386 (Japan Trench Paleoseismology) during the onshore phase. The onshore phase of expedition 386 took place between 2022-02-14 – 2022-03-15 onboard D/V Chikyu. After longitudinal splitting of the core sections, high-resolution (100 pixels/cm) images of archive half was captured using the Tri-Sensor Core Logger (TSCL; NS Design). The camera provides a 16-bit red-green-blue (RGB) color (48-bit) TIFF file from which the RGB data were derived in 1 mm down-core resolution. For each section: 1) the TIFF file (from line scanning) full resolution was opened and channels scaled to 0-255; 2) TIFF file cut at top (2475 px) and bottom (2470 px + length of the section x resolution); 3) for every line of pixel down section, R, G, B values were averaged over a width of 450 px across the centre of the section (\~4.5 cm width) and data placed into a table compiling all sections of a hole; 4) for every depth interval, where a piece of sponge was observed on the linescan, R, G, B data were deleted; 5) R, G, B data were also deleted to the top and bottom ~1 cm of each section, to account for possible gaps or pieces of liner. For further methodological information see methods chapter in0.167emStrasser, M. et al., 2023 https://doi.org/10.14379/iodp.proc.386.102.2023